Penanaman Nilai Toleransi Melalui Pembelajaran IPS di Sekolah Dasar - Ika Novita Maharani; Alma Pratiwi Husain (Journal of Humanities, Social Sciences, and Education, 2026)
Character education is a crucial foundation for developing responsible, honest, and disciplined individuals capable of interacting harmoniously with their social environment. This study aims to analyze the implementation of character education values ​​in Social Studies (IPS) learning at SD Inpres Arso 9. The study employed a qualitative descriptive method with a content analysis approach and a systematic literature review. Data were obtained through interviews with the principal and fifth-grade teachers, as well as documents in the form of thematic IPS textbooks based on the 2013 Curriculum. Data triangulation was conducted to ensure validity through the involvement of the researcher as an instrument, careful observation, and theory verification. The results indicate that the implementation of character education is carried out through three main phases: planning, implementation, and assessment. During the planning phase, the school socializes the curriculum, develops regulations, and plans the integration of character values ​​into the syllabus and lesson plans. The implementation phase includes instilling positive character values ​​through classroom learning, habituation, conditioning the school environment, as well as integrating local culture and the use of visual media. Assessment is conducted by observing student behavior during learning, so that the internalization of values ​​can be monitored and developed. Social studies learning has been proven effective in instilling moral principles, such as religiosity, honesty, discipline, responsibility, tolerance, cooperation, patriotism, and social awareness. The success of character education is influenced by teacher readiness, school conditions, and family involvement. Therefore, developing a robust character education ecosystem requires collaboration between schools, families, and the community. The planned, contextual, and integrated implementation of character education produces students who excel academically while also being socially, emotionally, and morally mature, and able to face global challenges without losing their local cultural identity.